Optimizing the Molecular Diagnosis of GALNS: Novel Methods to Define and Characterize Morquio—A Syndrome‐Associated Mutations. Issue 3 (March 2015) - Caciotti, Anna; Tonin, Rodolfo; Rigoldi, Miriam; Ferri, Lorenzo; Catarzi, Serena; Cavicchi, Catia; Procopio, Elena; Donati, Maria Alice; Ficcadenti, Anna; Fiumara, Agata; Barone, Rita; Garavelli, Livia; et al.
<x xml:space="preserve">Abstract</x> We estabilished an array of techniques (QF‐PCR, CNV and CGH arrays): for the correct evaluation of MPS IVA patients' allelic composition, in order to achieve a diagnostic alogorithm to be used in the molecular analysis of MPS IVA syndrome: We characterised new identified mutations as a prerequisite to understanding the disease's natural progression in light of he incomming Enzyme Replacement Therapy for MPS IVA syndrome. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>